Klinis Polimiositis pada Kasus Lupus Eritematosus Sistemik: Sebuah Laporan Kasus - Wayan Sadhira Gita Krisnayanti; Putu Devara Karunia Esa; Kurnia Halim (Universitas Malahayati Lampung, 2024)
ABSTRACT Multiple organ involvement in Systemic Lupus Erythematosus (LES) cases is characteristic of a diverse clinical picture, one of which is skeletal muscle tissue. This occurs because LES is an autoimmune disease that can chronically attack body tissues which have an impact on the patient's clinical presentation. The aim of this case report is to present the clinical presentation, examination, and management of polymyositis in systemic lupus erythematosus. A 28-year-old woman with complaints of pain in large joints, there are other complaints such as bruises on both legs, fever that does not arise, mouth ulcers that are difficult to heal pounding, weight loss of 6 kg within one month while the patient's appetite increases, angry spots on the neck that spread to the face, chest, both hands and sometimes itching and weakness in the left leg. The diagnosis of LES was based on the American College of Rheumatology diagnostic criteria. The diagnosis of polymyositis was based on Bohan and Peter's classification criteria for polymyositis and dermatomyositis. The patient was treated with Methylprednisolone 1x8 mg, Azathioprine 3x50 mg and Hydroxychloroquine (HCQ) 1x200 mg. In conclusion, the clinical presentation of Polymyositis in LES patient treated with Corticosteroid, Immunosuppressive, and HCQ gave satisfactory outcome to improve the clinical and patient's markers. Keywords: Systemic Lupus Erythematosus, Polymyositis, Lupus Myositis, Autoimmune. ABSTRAK Keterlibatan banyak organ pada kasus Lupus Eritematosus Sistemik (LES) merupakan karakterisktik dari gambaran klinis yang beragam, salah satunya jaringan otot rangka. Hal ini terjadi karena LES merupakan penyakit autoimun yang dapat menyerang jaringan tubuh secara kronis yang berdampak kepada presentasi klinis pasien. Tujuan laporan kasus ini adalah menyajikan presentasi klinis, pemeriksaan, dan manajemen polimiositis pada lupus eritematosus sistemik. Perempuan usia 28 tahun dengan keluhan nyeri pada sendi besar, terdapat keluhan lain seperti lebam-lebam pada kedua tungkai, demam yang hilang timbul, sariawan yang sulit sembuh berdebar, berat badan turun 6 kg dalam waktu satu bulan sedangkan nafsu makan pasien bertambah, bercak kemarahan di leher yang menyebar hingga ke wajah, dada, kedua tangan dan terkadang gatal serta terdapat kelemahan pada tungkai kiri. Diagnosis LES didapatkan berdasarkan kriteria diagnostik American College of Rheumatology. Diagnosis polimiositis berdasarkan kriteria klasifikasi Bohan dan Peter untuk polimiositis dan dermatomiositis. Pasien diterapi dengan Methylprednisolone 1x8 mg, Azathioprine 3x50 mg dan Hydroxychloroquine (HCQ) 1x200 mg. Kesimpulan dari presentasi klinis pasien Polimiositis pada LES yang diterapi dengan Kortikosteroid, Imunosupresif, dan HCQ memberikan luaran yang memuaskan untuk memperbaiki klinis dan petanda pasien. Kata Kunci: Lupus Eritematosus Sistemik, Polimiositis, Miositis Lupus, Autoimun